Accreditation of The Hydrographic Surveying Course at UCL and The PLA - Iliffe, J. C.; Greenland, A. J. (The International Hydrographic Review, 2001)
In September 1999, the Department of Geomatic Engineering at University College London (UCL) introduced a new MSc in Hydrographic Surveying, in partnership with the Port of London Authority (PLA). In May 2001 this degree programme was approved by the courses board of the International Hydrographic Organisation and the International Federation of Surveyors as a Category A course. The aim of this article is to explain the background to the partnership between UCL and the PLA, and to describe how the course has been designed to meet the IHO/FIG criteria.